Genetically modified Pichia pastoris, a powerful resistant factory for gold and palladium bioleaching and nanostructure heavy metal biosynthesis - Fatemeh Elahian; Razieh Heidari; Vahid Reza Charghan; Elham Asadbeik; Seyed Abbas Mirzaei (Artificial Cells, Nanomedicine, and Biotechnology, 2020)
A metal-resistant engineered Pichia pastoris was developed here to fulfil the metal bioleaching in aqueous conditions. Parent and recombinant yeasts were grown in YPD medium containing different concentrations of ion metals. XRD, electron microscopy and particle size analyser were used for the characterisation and the nanoparticle analyses. The nanoparticle production kinetics were studied by ICP-OES. The cytotoxicity of nanoparticles was assayed against human cell lines. Media colours changed to a range from purplish-brown to grey during early fermentation stages. The maximum biosorption capacities were recorded 81.23 and 493.35 mg/g for gold and palladium in batch conditions, respectively. Various physical investigations proved monodispersed spherical nanoparticles around 100 nm in size. Pure palladium nanoparticles and PdCl2 represented the least cytotoxic potency towards T47D and EPG85.257 cells. The results demonstrated that the genetically modified yeast is a cost-effective, high-throughput, robust, and facile system for metal biosorption.